2014
DOI: 10.3109/0886022x.2014.982954
|View full text |Cite
|
Sign up to set email alerts
|

Bcıı—RFLP profiles for serum amiloid A1 and mutatedMEFVgene prevalence in chronic renal failure patients requiring long-term hemodialysis

Abstract: Background and aim: There is an increased mortality risk in long-term hemodialysis patients of renal failure due to the chronic inflammation. The relationship between the chronic renal failure (CRF) and the role of familial genetic markers remains incompletely understood. In the current study, it was aimed to find out the prevalence of common MEFV gene mutations and BcII polymorphism in serum amyloid A1 (SAA1) gene in chronic renal patients (CRF) who require long-term hemodialysis. Method: Current cohort inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…MEFV gene has ten exons and encodes pyrin protein, consisting of 781 amino acids (The International FMF Consortium 1997). FMF are common especially in Jews, Arabs, Armenians, and Turks (Livneh et al 1997;Ozdemir et al 2015;Ş ahin et al 2015). Population screening in Central Anatolia region of Turkey revealed that M694V is the most frequent mutation in MEFV gene, followed by E148Q, M680I (G/C) and V726A (Ozdemir et al 2011;Koksal et al 2009;Huzmeli et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…MEFV gene has ten exons and encodes pyrin protein, consisting of 781 amino acids (The International FMF Consortium 1997). FMF are common especially in Jews, Arabs, Armenians, and Turks (Livneh et al 1997;Ozdemir et al 2015;Ş ahin et al 2015). Population screening in Central Anatolia region of Turkey revealed that M694V is the most frequent mutation in MEFV gene, followed by E148Q, M680I (G/C) and V726A (Ozdemir et al 2011;Koksal et al 2009;Huzmeli et al 2016).…”
Section: Introductionmentioning
confidence: 98%
“…It is important to form a clinical picture of FMF in Turkey, especially in the province of Sivas where FMF is most frequently observed [12][13][14]. Screening of individuals who have FMF in their family histories and evaluating the treatments of phenotype III cases that have mutations but do not show clinical symptoms are prominent issues to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…The MEFV gene, located on chromosome 16p13.3 and encoding a protein called pyrin, is responsible for Familial Mediterranean Fever (FMF) disease. Mutations in the MEFV gene have been found in the majority of FMF patients [11][12][13][14]. The vast majority of MEFV mutations identified in FMF patients include mutations (M680I, M694V, M694I, and V726A) clustered in exon 10 and a mutation in exon 2 (E148Q) [15].…”
Section: Introductionmentioning
confidence: 99%
“…In chronic kidney function injury process, endotoxin in the body cannot be metabolized in time, and toxin retention in the body of patients will cause damage to their kidney function, forming a vicious circle as patient's chronic kidney function was injured [2,3]. Base on the reports, hemodialysis can effectively remove the toxin molecules in the blood and control the progression of the patient's disease in chronic kidney patients [4,5]. However, in hemodialysis process, patients affected by the condition, patient easy to produce bad emotion.…”
Section: Introductionmentioning
confidence: 99%